The ignored middle: Transition from first to second year financial accounting - Baard, R.; Steenkamp, L.; De Jager, E. (South African Journal of Higher Education, 2025)
In higher education, the transition from first year to second year is marked by unique challenges, often underestimated by both students and educators. While extensive research has explored the transition from school to university, limited attention has been directed towards the transition between the first and second years of higher education. This article aims to explore the impact of a specific first-year Financial Accounting module on student success in a second-year Financial Accounting module at a South African university. By examining the factors that facilitate or hinder this transition, the study sought to bridge the gap between student expectations and the realities of their academic journey. The study investigated whether, according to the perceptions of students, a specific first-year Financial Accounting module supports or fails to support student success in a specific second-year Financial Accounting module at one South African university. In addition, the study set out to determine what students perceived to be the major influences on their success or failure in Financial Accounting at second-year level. The research aimed to give a descriptive analysis of the perceptions of students, which were empirically investigated by means of a questionnaire, containing both open and closed questions. The results revealed that, according to the perceptions of the respondents, the first-year module prepared them adequately to complete the second-year module successfully. However, the respondents indicated that the way in which the first-year module is presented creates incorrect expectations of the second-year module. Suggestions to ease the transition between the two years of studies included better communication in the first-year module regarding future expectations, as well as introducing second-year topics in the first year already. While the results of this study mainly reflected students’ own perceptions, the research question identified is not necessarily restricted to a specific discipline. The findings could be generalisable beyond this context to other disciplines and other higher education institutions